1968
DOI: 10.1530/jrf.0.0150325
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation and Fertilization in the Lamb

Abstract: The experiments described below were undertaken to study the effects of different hormone treatments on follicular development, ovulation and fertilization in lambs. In a similar investigation, Mansour (1959) obtained a low rate of fertilization which he attributed to the use of diluted semen and to the inefficiency of insemination by the vaginal route. In the present experiments fresh undiluted semen was introduced directly into the uterine horns.Sixteen Scottish Blackface and eight crossbred female lambs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1975
1975
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…The present results confirm previous reports (Mansour, 1959;Land & McGovern, 1968) Gates, 1956; pig: Baker & Dziuk, 1970). However, in the calf only limited development of embryos has been obtained (Onuma & Foote, 1969;Seidel, Larson, Spilman, Hahn & Foote, 1971 The process by which exogenous progesterone increases ovulation rate in lambs is not known and has not been reported previously, although Land & McGovern (1968) suggested that progest¬ erone may increase follicular development when large doses of PMSG are used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present results confirm previous reports (Mansour, 1959;Land & McGovern, 1968) Gates, 1956; pig: Baker & Dziuk, 1970). However, in the calf only limited development of embryos has been obtained (Onuma & Foote, 1969;Seidel, Larson, Spilman, Hahn & Foote, 1971 The process by which exogenous progesterone increases ovulation rate in lambs is not known and has not been reported previously, although Land & McGovern (1968) suggested that progest¬ erone may increase follicular development when large doses of PMSG are used.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, ovulation may be induced in lambs at 8 weeks of age and older by treatment with progesterone and gonadotrophins (Mansour, 1959) and cleavage of such ovulated eggs may be obtained after intra¬ uterine insemination (Land & McGovern, 1968). However, there has been no detailed examination of the normality of fertilization, embryo development, luteal function and ovarian follicular steroid¬ ogenesis in prepubertal lambs.…”
Section: Introductionmentioning
confidence: 99%
“…From several studies on ovaries from lambs between 10 and 32 weeks of age it has been noted that they are able to secrete steroids, ovulate and produce fertilizable ova in response to PMSG and/or hCG (Mansour, 1959;Land & McGovern, 1968;Trounson et ai, 1977). The also Trounson et ai, 1977;Tassell et ai, 1978;Tassell & Kennedy, 1980 (Hillier, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…The follicles are able to respond to exogenous gonadotrophins and ovulation may be induced (Mansour, 1959). If intrauterine insemination is used to bypass the cervical block, the eggs ovulated may be fertilized (Land & McGovern, 1968), and when transferred to adults at an appropriate stage of the oestrous cycle they develop normally (Trounson, Willadsen & Moor, 1977). The latter authors also demonstrated that the capacity of the lamb follicle to secrete oestrogen, testosterone and progesterone in vitro was similar to that of the adult.…”
Section: Genetic and Seasonal Variationmentioning
confidence: 97%